Perbedaan Self Wound Care Pasien Diabetes Mellitus Tipe 2 Dengan Pendidikan Kesehatan: Video - Sudaryanto, Sudaryanto; Hando, Ananda Fero (Universitas Pahlawan Tuanku Tambusai, 2024)
Diabetes mellitus (DM) is a disease that is a global problem. A person is said to be suffering from DM if their blood sugar level 2 hours after eating is >200 mg/dl. Apart from being a cause of death, DM can also cause various complications, one of which is diabetic ulcers. This type of research is quantitative with quasi-experiment and one group pretest posttest design. The research sample was 30 respondents using consecutive sampling. Data analysis using the paired T test to determine the effect of providing Health Education interventions using audio-visual video media on self-wound care skills. The results showed that respondents' self-wound care skills before the intervention: mean respondent skill score 26, 833, standar deviation D 7.4015, lowest score 15.0 and highest 39. Self-wound care skills after intervention: mean respondent skill score 45, 950 , standar deviation 13.5203, the lowest value 25.0 and the highest 71.5. The results of the paired T test show the effect of health education using videos on respondents' self-wound care skills (Sig 2 tailed 0.000 <0.05). Health education with videos influences respondents' self-wound care skills at the Mumtaza Clinic, Sragen.